A Mapping Study of Veterinary Literature on Perceptions and Attitudes of Female Canine Spaying - Fausak, Erik Davis (Frontiers in Veterinary Science, 2020)
This is a mapping study conducted to evaluate the characteristics of where content that engages in perspectives or attitudes on female dog spaying is published. Three databases, CAB Direct, PubMed, and Scopus, were systematically searched. There were 84 out of 642 papers identified and screened for relevance on attitudes or perceptions on female canine spaying. These 84 articles were then examined for recurring authors, institutional representation, and publisher information. Additionally, information regarding the population being addressed, veterinarian or client, was noted with most literature addressing the veterinary perspective. Many important articles were published in a wide array of journals from many countries, which suggests the importance of not only browsing journals but also searching for relevant literature in databases like CAB Abstracts and MEDLINE.